Estrogen receptor-negative breast ductal carcinoma: clinicopathological features and MIB-1 (Ki-67) proliferative index association. - Noorasmaliza Mdpaiman; Siti Aishah Md Ali; Reena Mdzin; Meor Zamari Meor Kamal; Wan Anna Md Amin; Mohan Nallusamy; Pavitratha Puspanathan; Rohaizak Muhammad; Sharifa Ezat Wan Puteh; Srijit Das (PLoS ONE)
Breast cancer estrogen receptor (ER) status is one of the strong additional factors in predicting response of patients towards hormonal treatment. The main aim of this study was to assess the morphological characteristics and proliferative activity using MIB-1(Ki-67) of estrogen receptor negative invasive breast ductal carcinoma (NOS type) as well as to correlate these features with clinicopathological data. We also aim to study the expression of c-erbB2 in ER negative breast tumors. High proliferative rate (MIB-1 above 20%) was observed in 63 (63.6%) of 99 ER negative tumors and that these tumors were associated with high expression of c-erbB2 (57.6%). We observed that MIB-1 is a reliable independent prognostic indicator for ER negative infiltrating ductal carcinoma in this study.